Validación del método de análisis (4500 NO3-B) "screening", para la determinación de nitratos en agua potable mediante la técnica de espectroscopia ultravioleta - Rios Acevedo, Jhon Jairo (Universidad Santiago de Cali, 2020)
The method UV spectroscopy was validated for the determination of nitrate in drinking water samples for human consumption. Evaluation was made linear range was found that the expectation determine analyte is between 0.5 and 10.0 mg/L with a correlation coefficient (r) of 0.9997 at a wavelength 220 nm. The minimum detectable and quantifiable analytical conditions developed under this method are 1.26 and 1.33 mgNO3- /L respectively. The accuracy was found a coefficient of variation for repeatability in spiked samples at low and high levels between 0.17%-0.21 % and 0.14%-0.25 % respectively and for reproducibility coefficient was found variation in spiked samples at low and high levels between 0.20%-0.26 % and 0.26%-0.30 % respectively. The analyte recoveries were between 101.0 % and 105.2 %.